Population density and health condition of Cladocora caespitosa in the shallow zone of the Amvrakikos Gulf (Ionian Sea - Western Greece) - ELENI GAVRIEL; PAVLOS AVRAMIDIS; CONSTANTIN KOUTSIKOPOULOS; ALEXIS RAMFOS (Mediterranean Marine Science, 2026)
The Mediterranean coral Cladocora caespitosa is a key species in temperate marine ecosystems, contributing to reef-building processes. However, it faces increasing threats from climate change, pollution, and human activities, in shallow coastal areas in particular This study presents a baseline monitoring project implemented in the Amvrakikos Gulf, Greece, in order to assess the distribution, health, and environmental drivers of C. caespitosa. A total of 26 sampling sites were surveyed across different depth zones and substrate types. Data collection included photographic documentation, in-situ morphometric measurements, and qualitative assessment of colonies at different substrate types and depths. The results show that the colonies on rocky substrates were significantly larger (118.2 ± 53.0 mm) than those on mixed rocky-sandy substrates (67.7 ± 44.8 mm). The average colony density across sites was 0.217 colonies/m², while only 12.5% of colonies were classified as fully healthy, with 56.05% exhibiting partial mortality. As expected, substrate type and depth were identified as key drivers of coral health and morphology. These findings provide useful baseline insights for conservation and management strategies, particularly for semi-enclosed Mediterranean basins vulnerable to climate change.

Comparative analysis of index-based and land cover-based C-factor estimation under wildfire disturbance in Western Greece - Maria Michalopoulou; Vasileios Boumpoulis; Pavlos Avramidis; Nikolaos Depountis (CATENA, 2026)

Mountainous vegetation succession and land use during the last millennium in the Peloponnese (southern Greece): Environmental change and economic development in an isolated periphery - Katerina Kouli; Georgios C. Liakopoulos; Grammatiki Vasileiadi; Dimitrios Lamprakis; Alexis Malliaris; Lucrezia Masci; Alessia Masi; Matthias Moros; Maria Papadaki; Cristiano Vignola; Pavlos Avramidis; Adam Izdebski (Journal of Quaternary Science, 2025)
Mediterranean mountainous areas and their valuable natural resources have long been attractive to human societies. The Peloponnese (southern Greece), with its complex topographic and climatic variability, has been the scenery for the development of numerous human communities. The existing paleovegetation records from the region derive mainly from lowland sites, while the vegetation succession of the mountains is not clearly understood. Herein, we focus on the sediment profile of Rakita, a wetland located in an isolated mountain basin in the northwestern Peloponnese. We combine pollen‐based vegetation reconstruction with detailed historical and archeological data and analyze them within a broader well‐connected region of the Peloponnese, characterized by an extensive coastline and central location in the Mediterranean trade system. In particular, we contextualize the pollen data with the detailed taxation registers, cadastres, and censuses produced by the Ottoman and Venetian authorities, which recorded agricultural production and population. The high‐resolution pollen profile covers the last 1100 years, and thus we are able to look at more than a millennium of socioeconomic change that witnessed a variety of political and economic systems that controlled the Rakita upland area. We are able to study how these different systems impacted the area of Rakita, which has sizable environmental potential for human exploitation, yet is not easily accessible, and therefore not the first choice for human actors whose goal was to maximize agricultural production of the region. We discover that a smaller scale non‐imperial but deeply market‐oriented political system of the late medieval period, such as the Principality of Achaea, was more successful in intensifying land use even in such isolated locations as Rakita than the large imperial systems of the Byzantine or Ottoman empires, even during their most intensive phases of growth.

Large-scale analysis of environmental and ecological impacts of marine finfish aquaculture in the Aegean and Ionian Sea (Eastern Mediterranean) - Sarah Faulwetter; Alexis Ramfos; Pavlos Avramidis (Science of The Total Environment, 2025)

Three-dimensional model and environmental fragility in the Guarani Aquifer system, SE-Brazil - Joaquim Ernesto Bernardes Ayer; Luca Lämmle; Ronaldo Luiz Mincato; Carlo Donadio; Pavlos Avramidis; Sueli Yoshinaga Pereira (Groundwater for Sustainable Development, 2024)

Monitoring the Kotychi Lagoon in Western Peloponnese, Greece, Using Remote Sensing Techniques and Environmental Assessment - Dionysios N. Apostolopoulos; Dionysios Giannikopoulos; Alexis Ramfos; Sara Faulwetter; Dionisios Panagiotaras; Konstantinos G. Nikolakopoulos; Pavlos Avramidis (Journal of Marine Science and Engineering, 2023)
The Kotychi Lagoon (western Peloponnese, Greece), together with other coastal wetlands such as Pappas, Prokopos and Lamia, is part of the wider area of the Strofylia Wetlands National Park and Protected Areas of Western Peloponnese, which has been protected by the Ramsar convention since 1971 and classified as a Natura 2000 area due to its high diversity and ecological value. This study aimed to estimate the water surface evolution of the Kotychi Lagoon using optical remote sensing techniques to record parameters and indices related to the geometrical and landscape orientation features for the 1945–2016 period and to evaluate the ecological and environmental status of the lagoon through in-situ measurement and sample analysis. High-resolution aerial photos at a scale of 1:30,000, orthomosaics, and satellite images were used and linear regression rates (LRR) were calculated to determine the changes. Seasonal sampling of water, sediment, and macrofaunal organisms in the lagoon was performed to monitor environmental and ecological parameters. The results showed that the lagoon’s water surface shrank during the 1945–2016 period, showing different rates in four segments. The shrinkage prevailed in the northeastern and southern parts of the lagoon, with rates of 17.75 and 6.46 m/year, respectively. The ecological status was determined to be poor, although nutrient input seemed to have been moderate over the study period. We conclude that applying remote sensing techniques using a combination of high-resolution images constitutes an effective and accurate method for the spatiotemporal mapping of wetlands. The ecological problems of the Kotychi Lagoon were highlighted and confirmed through complementary in-situ analyses. These problems need to be addressed by the respective managerial bodies in order to restore the lagoon to good ecological status.

Estimating Quantitative Morphometric Parameters and Spatiotemporal Evolution of the Prokopos Lagoon Using Remote Sensing Techniques - Dionysios N. Apostolopoulos; Pavlos Avramidis; Konstantinos G. Nikolakopoulos (Journal of Marine Science and Engineering, 2022)
The Prokopos Lagoon is part of the Kotychi Strofilias National Wetlands Park, which is supervised by the Ministry of Environment, Energy and Climate Change of Greece. The lagoon is situated at the northwestern coast of the Peloponnese and is protected by the Ramsar Convention. It is an important ecosystem with ecological services providing habitats for many plants and animals and essential goods and services for humans as well. No previous relevant studies for the wider wetland area are available, and given that lagoons are important ecosystems, their diachronic evolution should be under constant monitoring. Using remote sensing techniques in Geographic Information System (GIS) environment, alterations in critical parameters could be measured and applied for the protection of the area. The present study examines the spatiotemporal changes of the water extent of the Prokopos Lagoon, estimating landscape metrics and several morphometric parameters and indices related to the geomorphological features of the lagoon for the 1945–2021 period. Moreover, the adjacent shoreline was studied for each past decade evolution from 1945 to present, and it is discussed to whether there is a relationship between shoreline changes and the lagoon. High resolution satellite images and air photos at scale 1:30,000 were used to digitize the shorelines and the polygons of the lagoon’s surface. Linear Regression Rates (LRR), Net Shoreline Movement (NSM), End Point Rate (EPR) and Shoreline Change Envelope (SCE) provided by the Digital Shoreline Analysis System (DSAS) were used to determine the changes. Finally, future shoreline positions for 2021 and 2031 are estimated, while based on statistic models, we found that in the coastal area, the erosion–accretion cycle is predicted to be completed in 2031, after almost 86 years since 1945.

Assessment of clayey raw material suitability for ceramic production, in the Northern Peloponnese, Greece - Vayia Xanthopoulou; Ioannis Iliopoulos; Pavlos Avramidis (Archaeological and Anthropological Sciences, 2021)

Long-term effects of feral goats (Capra hircus) on Mediterranean island communities: results from whole island manipulations - Zachery S. Gizicki; Vanessa Tamez; Anastasia P. Galanopoulou; Pavlos Avramidis; Johannes Foufopoulos (Biological Invasions, 2018)